2017
DOI: 10.15406/mojboc.2017.01.00008
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Level of Dominant Mangrove Floral Species in Indian Sundarbans

Abstract: The astaxanthin level in the leaves of five dominant mangrove species, sampled from two different stations of Sager Island in western Indian Sundarbans region was studied during April, 2016. The two sampling stations selected at the northern and southern tips of the island exhibited drastic variation with respect to aquatic salinity, although other parameters like surface water temperature, pH, D.O. and nutrients were more or less uniform. Relatively higher astaxanthin level was observed in the high saline zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Previous studies also showed that mangroves contain unique pigments which may serve nutraceutical and pharmaceutical functions (Banerjee et al 2017). One of the mangroves has the potential to use its pigment content such as Rhizophora mucronata (Pringgenies et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also showed that mangroves contain unique pigments which may serve nutraceutical and pharmaceutical functions (Banerjee et al 2017). One of the mangroves has the potential to use its pigment content such as Rhizophora mucronata (Pringgenies et al 2018).…”
Section: Introductionmentioning
confidence: 99%